Sosialisasi dampak Bulying di SMK 1 Enrekang - Sura’, Handayani; Mulyadi, Mulyadi; Junaedi, Muhammad; Kamaria, Kamaria; Firman, Musda; Wahyuddin, Wahyuddin; Elihami, Elihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Human social life cannot be separated from interactions with each other. The development of social interactions will increase with age. Improving behavior in children really depends on the family. The family has an important role in teaching children and daughters how to behave properly and correctly, but if the family environment is not involved in an individual's social development, it will have an unfavorable impact, one of which is bullying. Bullying is carried out by a certain person or group to hurt someone physically or psychologically and make the victim traumatized and depressed. In this activity we try to participate in preventing bullying among students at SMK 1 Enrekang. The school environment is an environment that is very vulnerable to bullying behavior, so we carry out activities to provide education to students about the impact of bullying. In this activity we also play games that teach how to work together, tolerate and respect each other